A Research Study on The Development of Nanostructured Lipid Carriers for Furosemide Delivery: Formulation and Evaluation - Gond, Akshay; Thagele, Rajkumari; Gupta, M. K.; Kumar, Alok; Avinash, Avinash (Journal of Neonatal Surgery, 2025)
Designing and evaluating nanostructured lipid carriers (NLCs) to administer furosemide effectively, a strong loop diuretic with low oral bioavailability because of its substantial first-pass metabolism and low solubility, is the main focus of this study. NLCs were created to increase medication solubility, stability, and simplify controlled release. They are made up of a mixture of liquid and solid lipids stabilized by surfactants. NLCs loaded with furosemide were made via ultrasonography and thermal homogenization. The criteria employed to optimize various formulations included drug entrapment efficiency, zeta potential, particle size, polydispersity index (PDI), and in vitro drug release. A mean particle size of less than 200 nm was observed in the enhanced NLC formulation, which also had a narrow PDI and a zeta potential that suggested high physical stability. In order to confirm effective drug loading, the entrapment efficiency was noticeably high. The quick release from the pure medication was contrasted with a continuous release profile over a 24-hour period in in vitro release tests. Based on the data, NLCs may be a promising delivery method to increase furosemide's bioavailability and therapeutic effectiveness. It is necessary to conduct additional in vivo research to prove pharmacokinetic benefits